Penggunaan Virtual Reality (VR) Untuk Simulasi Interaksi Multikultural Dalam Mengembangkan Toleransi Siswa - Septian, Muhammad Rezza; Annisa, Dona Fitri; Siddik, Riesa Rismawati (Jurnal Pengabdian Masyarakat, Ilmu, dan Aksi, 2025)
In the era of globalization, the ability to interact in a multicultural society is an important skill that must be possessed by the younger generation. However, many students still have difficulty in understanding and appreciating the value of tolerance due to limited cross-cultural experience. This community service activity aims to improve students' understanding and empathy for cultural diversity through a psychoeducational approach and the use of Virtual Reality (VR) technology at SMKS Maarif Terpadu Cicalengka. This program involved 70 students and three BK teachers, and was carried out through three stages of activities: psychoeducation, interactive lectures, and discussion sessions. The method used was qualitative-descriptive with a participatory approach, equipped with pre and post questionnaires and direct observation. The results of the activity showed that the use of VR in multicultural interaction simulations succeeded in increasing students' cognitive and emotional awareness of the importance of tolerance, as well as encouraging changes in attitudes towards a more inclusive direction. These findings strengthen the argument that the integration of immersive technology such as VR, when applied appropriately and contextually, can be an effective approach in character education and strengthen the values ​​of diversity among students.